THE USE OF MULTIMODALITY IN “AXE” TV COMMERCIALS TO COMMUNICATE MASCULINITY - Novita Magdalena Srikandiati; V. Luluk Prijambodo (Widya Mandala Surabaya Catholic University, 2015)
Advertisements in the digital era creatively make use of writing, speech, images, and music to promote goods and services. This multimodality is used to persuade customers. Likewise, TV commercials have adopted multimodality for “a creatively communicative interaction” to support the goods and services advertised. Some studies on multimodality on media have been conducted but those on advertisements are still scarcely done, especially in Indonesia. Importantly, advertisements as sample of short functional texts belongs to curriculum aspects of the English subject for the students of the ninth grade in Indonesia (the Ministry of Education and Culture, 68, 2013). The TV commercials of “Axe” perfume product attracted the writer to conduct a research on multimodality. The English version of “Axe” TV commercials was chosen as the case under study. The analysis done indicated that “Axe” TV commercials contained a set of chronologically effective organization of multimodality which represented a set of creative sequence of the use of language, images and music to signify a persuasive, advertisement discourse attribute.